(untitled) (Theatrum historiae, 2006)
All who positively perceive the Summerhill school, celebrated in the year 2003, 120 years from the birth and 30 years from the death of its founder A.S. Neill (1883-1973). This school refers to the boarding school which has been in existence continuously until today since 1924. From the beginning, the Summerhill School was opened for children having educational problems, later on, its creator himself classified the school as a therapeutic school for normal children. The school is based on the principle of confidence and partnership between boarders and adults, Neill left the children freedom and created conditions for self-education within the framework of self-governing organisation of the school life. Neill is an author of many publications in the field of children´s pedagogy and psychology. The influence of this institute upon the present education has always been incomparable to the number of school-leavers. This an oldest running school having an almost unchanged autonomy offering optional presence in lessons.